Interspecies transmission of macaque simian T-cell leukemia/lymphoma virus type 1 in baboons resulted in an outbreak of malignant lymphoma - Alexander F. Voevodin; Elena Samilchuk; Hermann Schätzl; Enzo Boeri; Genoveffa Franchini (1996)
An outbreak of malignant lymphoma has been observed in one of the baboon (Papio hamadryas) stocks of Sukhumi Primate Center. More than 300 cases in this "high-lymphoma stock" have been registered since 1967. Human T-cell lymphotropic virus type 1 (HTLV-1)-related virus was implicated as the etiologic agent of Sukhumi baboon lymphoma. The origin of this virus remained unclear. Two possibilities were originally considered: the origin could be baboon simian T-cell leukemia/lymphoma virus type 1 (STLV-1) or HTLV-1 (before the outbreak started, some Sukhumi baboons were inoculated with human leukemic material). The third possibility entered recently: interspecies transmission of rhesus macaque STLV-1 to baboons. It was prompted by the finding of very close similarity between STLV-1 991-1cc (the strain isolated from a non-Sukhumi baboon inoculated with material from a Sukhumi lymphomatous baboon) and rhesus STLV-1. To test this hypothesis, we investigated 37 Sukhumi STLV-1 isolates from baboons of high-lymphoma stock by PCR discriminating rhesus type and baboon type STLV-1 isolates. All of them were proved to be rhesus type STLV-1. In contrast, all six STLV-1 isolates from baboons belonging to other stocks or populations were of baboon type. The PCR results were fully confirmed by DNA sequence data. The partial env gene gene sequences of all four STLV-1 isolates from Sukhumi lymphomatous baboons were 97 to 100% similar to the sequence of known rhesus STLV-1 and only 85% homologous with the sequence of conventional baboon STLV-1. Thus, interspecies transmission of STLV-1 from rhesus macaques (or closely related species) to baboons occurred at Sukhumi Primate Center. Most probably this event initiated the outbreak of lymphoma in Sukhumi baboons.